Making Visible the Invisible. Augmented Reality Visualization for 3D Reconstructions of Archaeological Sites - Pierdicca, Roberto; Frontoni, Emanuele; Zingaretti, Primo; Malinverni, Eva Savina; Colosi, Francesca; Orazi, Roberto (Augmented and Virtual Reality, 2015)
In archaeology, findings are completely freed from the earth which had been covering for centuries but in most cases they must be covered again in order to protect them. In this paper we present a augmented reality (AR) experience for the visualization of 3D models in-situ, giving the possibility to see conceived findings. The experience was carried out for archaeological purposes in Chan Chan, the America’s greatest pre-Columbian town. From 2001, our mission is operating at Chan Chan carrying on a wide action of documentation, conservation and exploitation. We propose an interesting workflow: image acquisition, 3D photogrammetric reconstruction, 3D simplification, AR visualization. Also a knowledge base applied to archaeological sites is here presented.